Identification of a Novel CYP11B2 Variant in a Family with Varying Degrees of Aldosterone Synthase Deficiency - Mark R. Garrelfs; Tuula Rinne; Jacquelien J. Hillebrand; Peter Lauffer; Merijn W. Bijlsma; Hedi L. Claahsen-van der Grinten; Nicole de Leeuw; Martijn J.J. Finken; Joost Rotteveel; Nitash Zwaveling-Soonawala; Max Nieuwdorp; A.S. Paul van Trotsenburg; et al. (Galenos Yayincilik, 2024)
Isolated aldosterone synthase deficiency is a rare autosomal recessive disorder caused by pathogenic variants in CYP11B2, resulting in impaired aldosterone synthesis. We report on a neonate with isolated aldosterone synthase deficiency caused by a novel homozygous CYP11B2 variant Chr8: NM_000498.3: c.400G>A p.(Gly134Arg). The patient presented shortly after birth with severe signs of aldosterone deficiency. Interestingly, segregation analysis revealed that the patient's asymptomatic father was also homozygous for the CYP11B2 variant. Biochemical evaluation of the father indicated subclinical enzyme impairment, characterized by elevated aldosterone precursors. Apparently, this homozygous variant led to different clinical phenotypes in two affected relatives. In this manuscript we elaborate on the biochemical and genetic work-up performed and describe potential pitfalls in CYP11B2 sequencing due to its homology to CYP11B1.